Inhibition of Brainstem Endoplasmic Reticulum Stress Rescues Cardiorespiratory Dysfunction in High Output Heart Failure - Diaz, Hugo S.; Andrade, David C.; Toledo, Camilo; Schwarz, Karla G.; Pereyra, Katherin; Diaz-Jara, Esteban; Marcus, Noah J.; Del Rio, Rodrigo (My University, 2021)
Recent evidence shows that chronic activation of catecholaminergic neurons of the rostral ventrolateral medulla is crucial in promoting autonomic imbalance and cardiorespiratory dysfunction in high output heart failure (HF). Brainstem endoplasmic reticulum stress (ERS) is known to promote cardiovascular dysfunction; however, no studies have addressed the potential role of brainstem ERS in cardiorespiratory dysfunction in high output HF. In this study, we assessed the presence of brainstem ERS and its potential role in cardiorespiratory dysfunction in an experimental model of HF induced by volume overload. High output HF was surgically induced via creation of an arterio-venous fistula in adult male Sprague-Dawley rats. Tauroursodeoxycholic acid (TUDCA), an inhibitor of ERS, or vehicle was administered intracerebroventricularly for 4 weeks post-HF induction. Compared with vehicle treatment, TUDCA improved cardiac autonomic balance (LFHRV/HFHRV ratio, 3.02 +/- 0.29 versus 1.14 +/- 0.24), reduced cardiac arrhythmia incidence (141.5 +/- 26.7 versus 35.67 +/- 12.5 events/h), and reduced abnormal respiratory patterns (Apneas: 11.83 +/- 2.26 versus 4.33 +/- 1.80 events/h). TUDCA administration (HF+Veh versus HF+TUDCA, P<0.05) attenuated cardiac hypertrophy (HW/BW 4.4 +/- 0.3 versus 4.0 +/- 0.1 mg/g) and diastolic dysfunction. Analysis of rostral ventrolateral medulla gene expression confirmed the presence of ERS, inflammation, and activation of renin-angiotensin system pathways in high output HF and showed that TUDCA treatment completely abolished ERS and ERS-related signaling. Taken together, these results support the notion that ERS plays a role in cardiorespiratory dysfunction in high output HF and more importantly that reducing brain ERS with TUDCA treatment has a potent salutary effect on cardiac function in this model.
Keywords: apnea; chemoreceptor cells; endoplasmic reticulum stress; heart failure; sympathetic nervous system